Temperature Dependence of Solution-Induced Weakening of Compacted Snow. Issue 1 (January 2015) - Wåhlin, Johan; Klein-Paste, Alex
Snow that compacts on roads is difficult to remove and may become slippery at temperatures close to the melting point. To avoid snow compaction, chemicals are often applied before or during a snowstorm. Initially chemicals act by melting the snow. The solution that forms then reduces the ability of the snow to compact by weakening the bonds between individual snow crystals. Although the melting capacity of various chemicals has been thoroughly studied at different temperatures, the temperature dependence of the anticompactive effect that liquid solution has on snow is unknown. This anticompactive effect was studied in an experiment in which snow was mixed with a solution at equilibrium with ice and compacted to a constant dry density. The degree of compaction was indicated with a micropenetration hardness test. The experiment was performed at three temperatures: −2°C, −6°C, and −17°C (28°F, 21°F, and 1°F). The results showed that the liquid solution became less efficient at lower temperatures. To achieve the same snow hardness at −17°C, five and three times more solution was required than that required at −2°C and −6°C, respectively. At −6°C, approximately 1.7 times more solution was required than that required at −2°C. The combination of increased solution content at lower temperatures with the increased concentration required for a solution to remain liquid leads to a large increase in required salt application as the temperature decreases. This combination likely contributes to chemicals losing their practical effectiveness in winter maintenance at temperatures substantially higher than the eutectic temperature.